O processamento de homógrafos interlinguísticos do inglês para o português brasileiro durante a tradução - Mota, Iakob Lourenço (2024)
This study explores the intertwined concepts of translation, bilingualism and bilingual lexical access methods, shedding light on their historical evolution and their significance in today's multilingual world. Starting with a glimpse into the origins of translation, we delve into the rich history of this fundamental practice, tracing its development from ancient times to the modern era. From religious texts to literary masterpieces, translation has played a vital role in bridging cultures and facilitating global communication. Further on, the dissertation deepens into the scope of bilingualism, highlighting its impact on language acquisition and cognitive processes. By studying the historical context and ongoing research, we gain valuable insights into the complexities of bilingualism in an increasingly globalized and pluralistic society. Furthermore, the study investigates the field of bilingual lexical access methods, exploring how bilingual individuals access and process their linguistic knowledge. We discuss several theoretical frameworks and computational models that have been developed to understand the complexities of bilingual lexical processing (Kroll; Stewart, 1994; Kroll; De Groot, 1997; Dijkstra; Van Heuven; Grainger, 1998; Dijkstra; Van Heuven, 2002; Dijkstra et al., 2018). These methods encompass different cognitive mechanisms involved in lexical retrieval and language selection, clarifying the dynamic nature of the bilingual subject's processing. This study aims to analyze the reaction time and accuracy in the translation of interlingual homographs from the English – Brazilian Portuguese language pair with the purpose of verifying what effects this class of words has on the translation. To collect the data, Psytoolkit software (Stoet, 2010, 2017) was used, which operates online, capturing the reaction time of responses. The study corpus was fed into the software and, after data collection, the analysis was carried out in RStudio, an application dedicated to data processing and analysis. After the analysis, it was possible to observe an interference effect of interlingual homographs for accuracy and response time. The results obtained add to the discussion about the use of translation as a research instrument on lexical access.